Reciprocal relationship between resilience and professional skills: a longitudinal study with social work students - Palma-García, María de las Olas; Gómez-Jacinto, Luís; Hombrados-Mendieta, Isabel (Taylor and Francis Group, 2018)
This study analyzed the relationship between the resilience developed by social work students and the professional skills acquired during their university degree program. A longitudinal study was conducted over 4 academic years. Participants were 73 social work students at the University of Malaga (Spain). The results show a gradual increase in the development of resilience and in the acquisition of professional skills among the students during the 4-year period. Panel model analysis shows that the two processes were stable and reciprocal throughout the social work training process. The results suggest that resilience had a stronger effect on professional skills than the latter had on resilience. In conclusion, resilience is a relevant component of university training of future social workers.
Keywords: Trabajadores sociales; Resilience; Social Work